2017
DOI: 10.3389/fmicb.2017.00659
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Adhesive Effect of Curcumin on Candida albicans Biofilms on Denture Materials

Abstract: The use of natural compounds as an alternative source of antimicrobials has become a necessity given the growing concern over global antimicrobial resistance. Polyphenols, found in various edible plants, offers one potential solution to this. We aimed to investigate the possibility of using curcumin within the context of oral health as a way of inhibiting and preventing the harmful development of Candida albicans biofilms. We undertook a series of adsorption experiments with varying concentrations of curcumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 49 publications
3
46
0
1
Order By: Relevance
“…In this study, the pre-treatment with Cur of both, disks (800 μg/mL for 10 min, corresponding to 50 μg/mL of Cur adsorbed to the surface) and C. albicans (50 μg/mL for 3, 30, and 90 min), significantly reduced adhesion of cells to an acrylic surface (70 and 27%, respectively). Moreover, a combined pre-treatment with Cur resulted in the greatest inhibition (93%) [43]. Those results highlight the potential of Cur as an effective anti-fungal and anti-biofilm agent.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In this study, the pre-treatment with Cur of both, disks (800 μg/mL for 10 min, corresponding to 50 μg/mL of Cur adsorbed to the surface) and C. albicans (50 μg/mL for 3, 30, and 90 min), significantly reduced adhesion of cells to an acrylic surface (70 and 27%, respectively). Moreover, a combined pre-treatment with Cur resulted in the greatest inhibition (93%) [43]. Those results highlight the potential of Cur as an effective anti-fungal and anti-biofilm agent.…”
Section: Discussionmentioning
confidence: 58%
“…Martins et al [42] observed that Cur alone was able to inhibit the adhesion of Candida species to BEC, and C. dubliniensis strains isolated from the oral cavity of HIV patients showed the most significant reductions (63 and 74%). Recently, it was also demonstrated that Cur had an anti-adhesive effect on a biofilm of C. albicans formed on acrylic surfaces [43]. In this study, the pre-treatment with Cur of both, disks (800 μg/mL for 10 min, corresponding to 50 μg/mL of Cur adsorbed to the surface) and C. albicans (50 μg/mL for 3, 30, and 90 min), significantly reduced adhesion of cells to an acrylic surface (70 and 27%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Lesions in the oral cavity often lead to diseases such as oral submucous fibrosis or stomatitis (20) and therefore play an important role as a symptom for immunodeficiency. During the infection process, colonization factors such as adhesins, invasins, and hyphae and their thigmotropic properties are of major importance (21). Together with Staphylococcus aureus, C. albicans has a much higher incidence of 11 to 65% for a stomatitis than in a monospecies biofilm (22).…”
mentioning
confidence: 99%
“…In the present review, mechanism action of antifungal activities against C. albicans were exhibited by metabolites of ten Indonesian medicinal plants, namely, allicin from A. sativum, 66 , curcumin 67 and xanthorrhizol 68,69 , envelope by eugenol 70 , membrane permeabilization by essential oils 71 , thymol 72 and diterpene 73 , and cell wall by terpenoids 36 , thymol 74 , and coumarin 27 . Metabolite from Indonesian medicinal plants mostly exerts their antifungal effects by growth inhibition, membrane, and cell wall active mechanism.…”
Section: Anti-candida Mechanism Of Action Of Indonesian Medicinal Plantsmentioning
confidence: 99%